The Influence of Financial Literacy, Overconfidence, and Locus of Control on Investment Decisions among Micro, Small, and Medium Enterprises (MSMEs) - Aksan, Fadriani; Goso, Goso; Mustafa, Sri Wahyuni (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of financial literacy, overconfidence, and locus of control on investment decisions of MSME actors in Palopo City. The research applied a quantitative approach with 120 respondents selected using saturated sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression, Confirmatory Factor Analysis (CFA), and path analysis with the assistance of SPSS and SmartPLS software. The findings indicate that financial literacy and overconfidence do not have a significant direct influence on investment decisions, while locus of control has a significant effect. Nevertheless, both financial literacy and overconfidence significantly influence investment decisions indirectly through locus of control.